2019
DOI: 10.1161/circulationaha.119.041399
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Valve Endocarditis After TAVR and SAVR

Abstract: Background: Prosthetic valve endocarditis (PVE) is a rare but critical mechanism of valve failure and death after transcatheter and surgical aortic valve replacement (TAVR, SAVR) warranting further analysis in modern aortic valve replacement experience. We characterize the incidence, risk factors, microbiological profile and outcomes of PVE from the PARTNER trials and registries (Placement of Aortic Transcatheter Valve). Methods: We analyzed a pooled co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
102
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 32 publications
11
102
5
Order By: Relevance
“…A metaanalysis of randomized trials in 3761 did not find an increased risk of IE in TAVI compared with SAVR [24]. Recently, the pooled analysis of all patients in PARTNER 1 and PARTNER 2 trials and registries reported that IE remains rare but often fatal in modern SAVR experience and that there was no difference in incidence, predictors, or risk of IE between TAVI and SAVR [25].…”
Section: Discussionmentioning
confidence: 99%
“…A metaanalysis of randomized trials in 3761 did not find an increased risk of IE in TAVI compared with SAVR [24]. Recently, the pooled analysis of all patients in PARTNER 1 and PARTNER 2 trials and registries reported that IE remains rare but often fatal in modern SAVR experience and that there was no difference in incidence, predictors, or risk of IE between TAVI and SAVR [25].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have evaluated the independent predictors of endocarditis following TAVR, and on multivariable analysis found, younger age, history of HF, need for permanent pacemaker placement, cardiac arrest, major bleeding, and sepsis were independently associated with an increased risk of endocarditis during follow‐up 19 . A recently published pooled analysis of patient‐level data from PARTNER 1 and 2 trials found no association between recent hospitalization for AS symptoms and endocarditis 20 . Nevertheless, the inclusion of PARTNER 1 patients who had high mortality rates, may have masked the effect of recent hospitalization on endocarditis due to competing risks.…”
Section: Discussionmentioning
confidence: 99%
“…19 A recently published pooled analysis of patient-level data from PARTNER 1 and 2 trials found no association between recent hospitalization for AS symptoms and endocarditis. 20 endogenous flora, depending on the length of hospitalization. 6 For example, bloodstream infections in patients who had been hospitalized for 2 or more days within 90 days prior to the infection were similar to nosocomial infections in terms of source of infection, pathogens and their antibiotic susceptibility patterns.…”
Section: Figurementioning
confidence: 99%
“…The present study reported no significant difference for in-hospital, early, mid-term, or late incidence of IE between patients with TAVI or SAVR. Summers et al (2019) reported a PVE incidence rate of 5.06 [95% CI, 4.19 to 6.12] per 1,000 person-years in PARTNER trials with no statistical difference in the incidence of TAVR and SAVR-PVE (Incidence rate ratio [IRR] 1.27 [95% CI, 0.70 to 2.32; P = 0.44]).…”
Section: Discussionmentioning
confidence: 99%